2012
DOI: 10.1002/anie.201102714
|View full text |Cite
|
Sign up to set email alerts
|

A Halide‐Induced Copper(I) Disulfide/Copper(II) Thiolate Interconversion

Abstract: One to two and back again: A disulfide–thiolate interconversion process in a dinuclear copper complex is induced by chloride ions (see scheme). Within this compound, the coordinating copper atoms serve either as electron source or as electron sink and thus oscillate between the oxidation states +I and +II.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
61
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(66 citation statements)
references
References 49 publications
3
61
2
Order By: Relevance
“…This conversion, in which Cu II is reduced to Cu I and the thiolate ligands are oxidized to form a disulfide bond, takes place intramolecularly and in some cases can be reversed in a controlled manner [11][12][13]. It has been reported that small ligand changes can determine the formation of either a Cu II l-thiolate or a Cu I disulfide complex [14].…”
Section: Introductionmentioning
confidence: 98%
“…This conversion, in which Cu II is reduced to Cu I and the thiolate ligands are oxidized to form a disulfide bond, takes place intramolecularly and in some cases can be reversed in a controlled manner [11][12][13]. It has been reported that small ligand changes can determine the formation of either a Cu II l-thiolate or a Cu I disulfide complex [14].…”
Section: Introductionmentioning
confidence: 98%
“…23 and 2 Cl 2 ] are synthetically connected by a chloride-induced disulphidethiolate interconversion. Disulphide cleavage and addition of chloride anions lead to significant structural changes; the six-membered Cu 2 S 4 -ring is transformed into a bis(μ-S) dicopper unit [86]. Table 14 illustrates the general tendency: upon oxidation of the coordinated copper ion, the C¼N bond stretches and the ρ-value increases.…”
Section: Guanidine-thio Ligandsmentioning
confidence: 98%
“…Addition of a methyl group next to the sulfur in the disulfide bond, however, results in significantly higher activity (entries [3][4][5][6]. Changing the bridge between the tertiary amine and the pyridyl groups from a methylene to an ethylene spacer at two positions leads to an increase in activity (entry 3 vs. 8), but at four positions it leads to a dramatic decrease in activity (entry 3 vs. 9).…”
Section: Dalton Transactions Papermentioning
confidence: 99%
“…[1][2][3][4][5][6] It has been reported that small changes in the ligand structure can direct the reaction with copper salts towards the formation of either a Cu II µ-thiolate or a Cu I disulfide complex and that these species can interconvert (Fig. 1a).…”
Section: Introductionmentioning
confidence: 99%